Alan Wake's Anxiety In Rick Burroughs' Alan Wake - Amelia Wahyu Larasati; Anik Cahyaning Rahayu (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
Anxiety disorders affect approximately 284 million people worldwide, yet the condition is frequently misread by sufferers as ordinary stress, delaying intervention until it compromises identity and relationships. This study analyzes the anxiety of Alan Wake, the protagonist of Rick Burroughs’ 2010 novel, using Sigmund Freud’s psychoanalytic theory to explore the mechanics of the ego's collapse under sustained threat. The objective is to describe the symptoms, causes, and effects of Alan’s anxiety to demonstrate it as a legitimate psychological condition. Employing a qualitative descriptive method and close reading, the study identifies three dimensions of anxiety. Findings reveal that symptoms manifest through visceral physical collapse, emotional distortions blurring reality and dreams, and behavioral paralysis—specifically a writer's block predating the novel's supernatural crisis by two years. Three interlocking forces drive this anxiety. the inescapable Dark Presence, the psychologically contagious Taken, and the moral guilt regarding his wife Alice’s disappearance, mapping onto Freud's realistic, neurotic, and moral anxiety respectively. The cumulative effects are total, including a fractured identity where Alan becomes a